An improper profession : women, gender, and journalism in late Imperial Russia - Gheith, Jehanne M.; Norton, Barbara T., 1948- (e-Duke books scholarly collection., 2001)
A contribution to understanding life in Imperial Russia through the work of contemporary women journalists.